2010
DOI: 10.1007/s10534-010-9290-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to cadmium induced oxidative stress in marine macroalga Ulva lactuca (Ulvales, Chlorophyta)

Abstract: This study describes various biochemical processes involved in the mitigation of cadmium toxicity in green alga Ulva lactuca. The plants when exposed to 0.4 mM CdCl(2) for 4 days showed twofold increase in lipoperoxides and H(2)O(2) content that collectively decreased the growth and photosynthetic pigments by almost 30% over the control. The activities of antioxidant enzymes such as superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR) and glutathione peroxidase (GPX) enhanced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 47 publications
(54 reference statements)
8
55
0
2
Order By: Relevance
“…The increased GR activity observed in G. domingensis after cadmium exposure could be related to the increased antioxidant defenses that result from Cd-induced oxidative stress. These results agree with those of Kumar et al [5], who demonstrated that the green alga Ulva lactuca also increased in GR activity after exposure to cadmium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The increased GR activity observed in G. domingensis after cadmium exposure could be related to the increased antioxidant defenses that result from Cd-induced oxidative stress. These results agree with those of Kumar et al [5], who demonstrated that the green alga Ulva lactuca also increased in GR activity after exposure to cadmium.…”
Section: Discussionsupporting
confidence: 93%
“…Heavy metals affect all biological organisms, especially those in the aquatic ecosystem, in many important ways. Several studies have shown effects such as the decrease of macroalgae growth rates [2], increased activities of glutathione reductase [5], changes in photosynthetic pigments [1,6] and photosynthetic efficiency [2,6], as well as an increase in total proteins and lipid contents [1]. Finally, some reports have shown changes in the ultrastructure of the red algae Audouinella savina (F. S. Collins) Woelkerling [7] and Ceramium ciliatum (J. Ellis) Ducluzeau [8], Hypnea musciformis (Wulfen) Lamouroux [6]; the green algae Dunaliella minuta Lerche [9], Enteromorpha flexuosa (Wulfen) J. Agardh [10], Euglena gracilis Klebs [1], and the brown algae Padina gymnospora (Kützing) Sonder [11].…”
Section: Introductionmentioning
confidence: 99%
“…We found that atr1, atr2, atr7, atr8 and atr9 showed less oxidative damage on cadmium compared to their background loh2 and the other lines (Fig. 2) wich correspond to our observation about phenotypic effect of cadmium on these mutants.. An induction of lipid peroxidation upon cadmium treatment was reported for Arabidopsis wild type seedlings, Arabidopsis plants, green alga Ulva lactuca, and in tomato plants respectively (50,30,55,4), while Gonçalves et al (22) demonstrated that MDA levels decreased under low concentartions of cadmium in cuccumber seedlings. …”
Section: Effect Of Cadmium On Lipid Peroxidationsupporting
confidence: 88%
“…Gonçalves et al (22) and Sandalio et al (51) demonstrated the reduction of total dry weight in cuccumber seedlings and pea plants respectively, while in wheat seedlings cadmium has an opposite effect (34) and low concentrations of cadmium slightly increased the chlorophyll content in barley seedlings (29). The reduction of growth upon cadmium treatment was observed in Arachis hypogaea seedlings (11) (55) and in green alga Ulva lactuca accompanied with decrease in photosynthetic pigments (30). …”
Section: Phenotypic Analysismentioning
confidence: 96%
See 1 more Smart Citation